Using transcriptomics to investigate the effects of infant formulae on the growth and development of small intestinal organoids and Caco2 cells - Xianli Wang; Yuxin Jing; Chengdong Zheng; Chenxuan Huang; Haiyang Yao; Zening Wang; Kainan Huang; Yuanyuan Yan; Shilong Jiang; Jianguo Sun; Qinggang Xie; Yongjiu Zhang; et al. (Journal of Functional Foods, 2025)
Infant formula serves as a crucial breast milk alternative, yet its molecular mechanisms remain poorly understood. Small intestinal organoids (SIOs) are in vitro-cultured, multicellular structures and have been applied in diverse research fields. Nevertheless, SIOs have not been used in formula studies, nor have comparisons been made between SIOs and traditional models. This study pioneered using SIOs alongside Caco-2 cells to investigate formula's effects through transcriptomics and RT-qPCR. Formula upregulated proliferation, differentiation, and structural pathways in both models. Comparative analysis (GO/KEGG/IPA) revealed SIOs enhanced protein metabolism, mucin/peptide secretion, and immune responses versus Caco-2 cells, with key pathway genes identified. Notably, lactoferrin and Bifidobacterium lactis synergistically improved extracellular matrix development and immune signaling. These findings provide mechanistic evidence of formula's cellular impacts using SIOs, establishing their superiority over traditional models for nutritional research. Our work offers novel insights for formula optimization while demonstrating SIOs' potential as an advanced intestinal model system.